From the League against Imperialism to Bandung: The Triumph of Territoriality - Shield, Jack (Institute of International Studies, 2025)
In his inaugurating speech at the Bandung Conference in 1955, Sukarno plucked out the League against Imperialism as an intellectual and organisational forebear. Yet, while this rightly situated Bandung in a longer history of anti-colonial activity, the discontinuities between these two conferences are equally illuminating. This article sets out to establish one of the legacies of Bandung by tracing backwards rather than forwards. I argue that while the League against Imperialism represented a more diffuse and de-territorialised vision of anti-imperialism, by the time of Bandung, the route from anti-colonialism to post-colonialism was clear: it ran through the territorial nation-state. Thus, the principal contribution of this article to this special issue is to draw attention to this legacy of territorialisation in Bandung. I trace some principal international ‘pulls’ that drove the push towards territoriality. Moreover, I contest the characterisation of Bandung as creating a “pluralist” international order since it rested on this consolidation around a territorial nation-state monoculture in global politics.